TOURISM MARKETING MANAGEMENT FRAMEWORK - Nurmahdi, Adi (International Humanities and Applied Science Journal, 2018)
The purposes of this paper is to deliver a conceptual model which enable Â analyzing insight to marketing strategy formulation and implementation of a local hospitality and tourism board administrator. Knowing organizational position in the market place is important and for that the Internal External (IE) matrix can be applied. In this model descriptive analysis method applied. Secondary data collected through the study of literature and other publication. The data analysis consists of external and internal environment assessments score, the marketing mix effectiveness, and Segmenting, Targeting and Positioning (STP) analysis. Matrix of the Grand Strategy carried out to overview options to the alternative strategies which the board has. This model suggests that a local hospitality and tourism board should increase its corporate strategies and competitiveness by distinguishably offering products which are different from its competitors, enhancing values offered to attractive tourist destinations, as well as considering local wisdoms and culture embedded in its product offering, so as simultaneously to raise local revenues which can be gained through the increase in the number of tourist visits, and the enhancement of many small medium enterprises and local economy for the betterment of societyâ€™s wellbeing